2017
DOI: 10.1093/geront/gnx051
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Environmental Factors With Quality of Life in Older Adults

Abstract: This study showed that multiple environmental factors are associated with quality of life in older people. To support independent living in older people health and social care professionals and policymakers may need to carry out interventions, in particular focusing on housing, residents, and nuisance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 44 publications
2
46
1
5
Order By: Relevance
“…The increase in the number of chronic diseases that accompanies older age [2], as well as numerous environmental factors affecting the life of aging individuals [3], significantly impact on their QOL [4]. Low QOL is reciprocally related to poorer health and decreased functioning of older adults [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the number of chronic diseases that accompanies older age [2], as well as numerous environmental factors affecting the life of aging individuals [3], significantly impact on their QOL [4]. Low QOL is reciprocally related to poorer health and decreased functioning of older adults [5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted to assess QQL among aging individuals have found that older age, gender, poor subjective health, depression, dependence and rural life [6], education and economic status [7], as well as chronic diseases [8], constitute a group of factors that negatively affect the QOL of older adults in several countries. Measuring QOL values among older adults and determining its associated factors have significant importance for introducing preventive interventions among older adults in a given region [4].…”
Section: Introductionmentioning
confidence: 99%
“…Czynniki środowiskowe (np. hałas, zatłoczenie, wzmożony ruch, ale także utrudniony dostęp do placówek związanych z utrzymywaniem i promowaniem zdrowia) mogą wpływać na jakość życia osób starszych, które często mają trudności z utrzymaniem właściwego funkcjonowania fizycznego, psychicznego i społecznego [4,5]. Dlatego w niniejszych badaniach miejsce zamieszkanie było główną zmienną różnicującą.…”
Section: Wprowadzenieunclassified
“…Ważnym aspektem w ocenie jakości życia tej grupy wydaje się pochodzenie. Badania pokazują, że istotne pod kątem zamieszkiwania zmienne charakterystyczne dla obszarów miejskich, takie jak sąsiedztwo, jakość powietrza, hałas, tempo, zatłoczenie, korelują z domeną środowiskową jakości życia [4]. W naszych badaniach dowiedliśmy, że mieszkańcy wsi uzyskali istotnie wyższe wyniki jakości życia w dziedzinie psychologicznej i środowiskowej niż mieszkańcy miasta, bez względu na płeć.…”
Section: Dyskusjaunclassified
“…People who live in an environment that has 80% or more green space reported longer sleep duration at night [29]. Other individual health practices such as smoking, drinking [30,31] [34,35]. A survey was conducted among Australian adults and found that environmental attributes including access to parks, bicycle and walking trails and the presence of greenness were positively related to physical and mental health [35].…”
Section: Introductionmentioning
confidence: 99%